The use of passive optical devices for the protection of information in fiber-optic communication lines and networks - Манько, Олександр Олексійович; Шматок, Олександр Станіславович; Петренко, Андрій Борисович (Ukrainian Information Security Research Journal, 2017)
Every year increases the amount of confidential information that is transmitted in optical communication networks. To ensure safe transmission of confidential information fiber optic lines are the most suitable. It is determined that the electromagnetic field of the light wave does not go beyond the optical fiber. However, under certain circumstances, interception of optical signal on the bend of the fibers is entirely possible. Thus, for the creation of optical lines with high level of information security are necessary additional measures. To this aim, in the proposed use of masking optical linear code by increasing the numbers of units are used passive components such as optical delay lines and optical splitters. The method allow increasing the number of units of code combinations to be transferred, and thus make it impossible for an adequate interpretation of the information. The advantage of the method is that the protection device is completely passive, and therefore reliable, and can be connected directly to the input and output of optical linear tract. Moreover, these devices do not require adjustment.